Tombs in Charandab- Tabriz - M Bazzaz-e Dastfroush; H Mir Jafari (متن شناسی ادب فارسی, 2009)
Charandab is one of the oldest lanes in Tabriz, where the most important cemeteries of Tabriz located. For the time being, only âthe ruined cemeteryâ including the box shaped gravestones has remained. The area in which the cemetery is now situated was clearly known until 1934, but after that constructing a new street destroyed the cemetery however, one could approximately determine its surroundings on the basis of the evidences available. The aim of this paper is studying the historical background and reports represented about the cemetery in different eras moreover, the researchers attempted inferring the biography of the literary men buried in the cemetery. The most important historical resources on Charandab and the buried men are Rozat Aljinan and Jinat Aljinan. These books, though, are mainly about the graves of the great men in Tabriz, they could provide the reader with valuable information on the historical neighborhood of Tabriz. Based on what remains along with maps at hand, it is possible to determine the area that the cemetery covers. This paper, also, consists of reviewing the researches on the matter of Charandab and the buried literary men there.